Does foreign aid reduce the country's risk of OFDI? The Chinese experience - Haijun Wang; Hu Yang; Fengya Li; Min Zhang (International Studies of Economics, 2023)
Abstract Using a sample of 124 countries assisted by China from 2000 to 2019, this paper examines the impact of foreign aid on outward foreign direct investment (OFDI) and the mitigation mechanism of risk. The research finds that, first, foreign aid can significantly reduce the country risk of recipient countries, especially political risk and financial risk, and thus play a role in promoting the inflow of OFDI of donor countries, and there is a lagged effect of this role; Second, foreign aid from other countries has a negative impact on China's OFDI to recipient countries, indicating that foreign aid is nonaltruistic and exclusive; Third, the mitigation effect of foreign aid on country risk is achieved through five channels: compensation effect, synergistic effect, pioneer effect, assimilation effect, and redistribution effects.